Evaluation of cost competitiveness of electric vehicles in Malaysia using life cycle cost analysis approach - Mustapa S.I.; Ayodele B.V.; Ishak W.M.; Ayodele F.O. (MDPI, 2023)
carbon emission; competitiveness; cost analysis; electric vehicle; life cycle analysis; policy making; pollution policy; strategic approach; Malaysia